The Correlation Between Self-Efficacy and Professional Identity in Medical Faculty Students - Febriyanti, Alisa; Permatasari, Tissa Octavira; Permana, Ouve Rahadian (Syntax Corporation, 2026)
Professional identity is an important aspect in the formation of the character and competence of a doctor and continues to develop throughout the process of becoming a doctor. Professional identity is influenced by external and internal factors. One of the internal factors is self-efficacy, which plays a role in encouraging one’s confidence in their ability to perform an action. This research aims to analyze the correlation between self-efficacy and professional identity among medical students at the Faculty of Medicine, Swadaya Gunung Jati University. This study used a cross-sectional design. The sample consisted of students in the academic and professional stages, with a total of 297 subjects selected using stratified random sampling. This study used primary data collected using the CASES and Professional Identity questionnaires. A total of 164 students (55.2%) had a good level of self-efficacy, while 133 students (44.8%) had a moderate level of self-efficacy. Regarding professional identity, 73 students (24.6%) had a very high level, 161 students (54.2%) had a high level, 59 students (19.9%) had a moderate level, and 4 students (1.3%) had a low level. There was a significant correlation (p-value = 0.001) between self-efficacy and professional identity, with a positive direction and weak correlation strength (correlation coefficient = 0.376). Thus, there was a significant correlation between self-efficacy and professional identity with a positive direction and weak correlation strength.